A Comparative Study on the Positive Lightning Return Stroke Electric Fields in Different Meteorological Conditions - Chin-Leong Wooi; Zulkurnain Abdul-Malek; Behnam Salimi; Noor Azlinda Ahmad; Kamyar Mehranzamir; Saeed Vahabi-Mashak (Advances in Meteorology)
Positive cloud-ground lightning is considerably more complex and less studied compared to the negative lightning. This paper aims to measure and characterize the significant parameters of positive return strokes electric field, namely, the zero-to-peak rise time, 10–90% rise time, slow front duration, fast transition rise time (10–90%), zero-crossing time, and opposite polarity overshoot relative to peak. To the best of the authors’ knowledge, this is the first time such detailed characteristics of positive lightning in Malaysia are thoroughly analyzed. A total of 41 positive lightning flashes containing 48 return strokes were analyzed. The average multiplicity is 1.2 strokes per flash. The majority of positive lightning was initiated from the primary positive charge rather than as a byproduct of in-cloud discharges. The cumulative probability distribution of rise time parameters, opposite polarity overshoot relative to peak, and slow front amplitude relative to peak are presented. A comparison between studies in four countries representing tropic, subtropic, and temperate regions was also carried out. Measured parameters in Florida, Sweden, and Japan are generally lower than those in Malaysia. Positive lightning occurrences in tropical regions should be further studied and analyzed to improve our current understanding on positive return strokes.